The Environs of Belgrade: Ethnological and Anthropological Research - Ivanović Barišić (Serbia), Milina (Bulletin of the Institute of Ethnography SASA, 2018)
The Belgrade vicinity is becoming more and more distinguishable as a separate regional unit - in the administrative, ethnic, economic and cultural terms. It is an extremely important area for ethnological and anthropological research bearing in mind the origin, way of life, material and spiritual heritage of the inhabitants. However, the surroundings of Belgrade have not yet been comprehensively explored. Past, relatively modest research, have shown that it is justified to focus the attention to the knowledge of traditional and modern habits of the inhabitants of the villages around Belgrade. This paper will present the results of the research of rural life in the surroundings of Belgrade, the connection of the city with the rural environment, and the changes caused by the influence of urban culture on the rural population. For that purpose, the results of previous researches of associates of the Institute of Ethnography SASA will be used. Key words: Belgrade environs, Belgrade, ethnological and anthropological research, second half of the 20th century